Knowledge Acquisition and Reverse Knowledge Transfer of Chinese Expatriates in Cross-Culture Context (UK) - HU, YUWEI (2017)
This paper intends to explore the knowledge acquisition and reverse knowledge transfer of Chinese expatriates. A semi-structured interview will be conducted with eight Chinese expatriates who have at least one-month expatriate experiences in the UK. In this study, language problem encountered each expatriates and tacit knowledge proved to be the most valuable knowledge obtained by expatriates. Technical convergence was found to cause expatriates decrease their willingness of transfer the knowledge. Additionally, the incentive from the parent company, the resonance between colleagues and a sense of belonging expatriates obtain from the company also become the factors that affect the expatriates’ knowledge sharing willingness. Despite the limitations of sample, this study successfully extended existing research on expatriate knowledge and transfer willingness in the knowledge transfer context by validating the types of knowledge they acquired and influencing factors on reverse knowledge transfer. The principal theoretical implication of this study is that it combined the reverse knowledge transfer with multinational corporations' expatriates, which has realized the cross integration of knowledge management and human resource management.